Deteriorating security, increased climate risks and uncertain geo-political relations: crossborder agropastoralism in transition - Acting for Life (International Livestock Research Institute, 2024)
In a collaboration between ILRI, the CGIAR Research Initiative on Fragility and Conflict, the SPARC programme (Cowater, ILRI, ODI and Mercy Corps), Acting for Life and their local partners RECOPA, UDOPER-AD, GEVAPAF-CIDeLS, CLIP and APAPE-PH, a regional dialogue was held within the Agropastoralism in Africa Conference 11th – 13th November 2024, to discuss these dynamics. The dialogue took the form of two consecutive sessions. The first session addressed the crossborder dynamics in the West African context, whilst the second focused on the various factors at play in farmer-herder conflicts in differing contexts, with case studies from Mali, Nigeria, Sudan and Kenya.